Role and clinical implications of atypical antipsychotics in anxiety disorders, obsessive-compulsive disorder, trauma-related, and somatic symptom disorders: a systematized review. (September 2016) - Albert, Umberto; Carmassi, Claudia; Cosci, Fiammetta; De Cori, David; Di Nicola, Marco; Ferrari, Silvia; Poloni, Nicola; Tarricone, Ilaria; Fiorillo, Andrea
Abstract : Atypical antipsychotics (AAs) may play a role in the treatment of anxiety disorders, obsessive-compulsive disorder (OCD), and trauma-related disorders. No reviews on their differential use in these different disorders have been performed recently. The aim of this systematized review was to obtain data on efficacy and comparative effectiveness of AAs as a treatment of anxiety disorders, OCD, and trauma-related disorders to provide guidance for clinicians on when and which AA to use. We searched on PubMed, Psychnet, and Cochrane Libraries from inception to July 2015. Search results were limited to randomized, placebo-controlled trials of adult patients. Evidence of efficacy was considered the presence of positive results in two or more double-blind placebo-controlled studies. Our systematized search identified 1298 papers, of which 191 were subjected to a full-text review and 56 were included. Quetiapine extended-release showed a role in both acute and maintenance treatment of uncomplicated generalized anxiety disorder, whereas more studies are needed before drawing practical recommendations on the use of olanzapine and risperidone; aripiprazole and risperidone are effective in resistant OCD as augmentation treatments. Risperidone and olanzapine add-on may have a role in resistant or chronic post-traumatic stress disorder patients, although only risperidone addition can be recommended on the basis of the criterion of two or more positive placebo-controlled trials. This systematized review supports the evidence that only a few AAs are effective in only a minority of the off-label conditions in which they are currently used and confirms that AAs are not all the same. Their use should be on the basis of a balance between efficacy and side effects, and the characteristics as well as the preference of the patient.